After the tone - Ang, Ashley Mun Fang (Nanyang Technological University, 2025)
After The Tone is a 14-minute documentary about grief and bereavement. As a topic that is often swept under the carpet, we have organised this film as a biography of grief through the lens of love, without shying away from the non-mutually exclusive pain it brings. We feature three profiles who have each lost a loved one. They bring us through their grief, in relation to their own lives as well as in relation to society – namely, interactions with others who do not know how to properly express their well-intended support, and the societal pressure to move on quickly. Through this film, we hope to impart to the audience a heightened level of grief literacy, and an informed version of empathy for the bereaved.